Antimicrobial resistance and AmpC production in ESBL-producing Klebsiella pneumoniae and Klebsiella quasipneumoniae: A retrospective study in Japanese clinical isolates - Watanabe, Naoki; Watari, Tomohisa; Otsuka, Yoshihito; Ito, Masahiko; Yamagata, Kazufumi; Fujioka, Miyuki (PLOS ONE, 2024)
The study of Klebsiella quasipneumoniae, Klebsiella variicola, and AmpC production in extended-spectrum β-lactamase (ESBL)-producing Klebsiella in Japan is limited, and existing data are insufficient. This study aims to characterize Klebsiella species, determine AmpC production rates, and analyze antimicrobial resistance patterns in ESBL-producing Klebsiella isolates in Japan. A total of 139 clinical isolates of ESBL-producing Klebsiella were collected in Japan, along with their corresponding antimicrobial susceptibility profiles. The isolates were identified using a web-based tool. ESBL genes within the isolates were identified using multiplex PCR. Screening for AmpC-producing isolates was performed using cefoxitin disks, followed by multiplex PCR to detect the presence of AmpC genes. Antimicrobial resistance patterns were analyzed across the predominant ESBL genotypes. The web-based tool identified 135 isolates (97.1%) as Klebsiella pneumoniae and 4 (2.9%) as K. quasipneumoniae subsp. similipneumoniae, with no instances of K. variicola detected. Among K. pneumoniae, the CTX-M-1 group emerged as the predominant genotype (83/135, 61.5%), followed by K. quasipneumoniae subsp. similipneumoniae (3/4, 75.0%). The CTX-M-9 group was the second most prevalent genotype in K. pneumoniae (45/135, 33.3%). The high resistance rates were observed for quinolones (ranging from 46.7% to 63.0%) and trimethoprim/sulfamethoxazole (78.5%). The CTX-M-1 group exhibited higher resistance to ciprofloxacin (66/83, 79.5%) compared to the CTX-M-9 group (18/45, 40.0%), a trend also observed for levofloxacin and trimethoprim/sulfamethoxazole. Among the 16 isolates that tested positive during AmpC screening, only one K. pneumoniae isolates (0.7%) were confirmed to carry the AmpC gene. Klebsiella pneumoniae with the CTX-M-1 group is the most common ESBL-producing Klebsiella in Japan and showed a low proportion of AmpC production. These isolates are resistant to quinolones and trimethoprim/sulfamethoxazole, highlighting the challenge of managing this pathogen. The findings underscore the importance of broader research and continuous monitoring to address the resistance patterns of ESBL-producing Klebsiella.